2016
DOI: 10.18632/oncotarget.11409
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in plasma cell-free DNA are diagnostic markers for esophageal squamous cell carcinoma recurrence

Abstract: ObjectivesEsophageal squamous cell carcinoma (ESCC) is one of the most aggressive malignancies owing to the high frequency of tumor recurrence. The identification of markers for early ESCC diagnosis and prediction of recurrence is expected to improve the long-term prognosis. Therefore, we searched for associations between tumor recurrence and cell-free DNA (cfDNA) mutations in blood plasma, which contains genetic markers for various cancer types.Experimental DesignGenomic DNA from tumors and cfDNA from plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…could show that higher ccfDNA levels after oesophagectomy are associated with poorer disease free survival of oesophageal squamous cell carcinoma patients 19 . Similar results were obtained by Ueda et al ., who describe the usage of somatic mutations in ccfDNA as a biomarker for post-surgical oesophageal squamous cell carcinoma recurrence 20 . The application of mutational analysis on ccfDNA for monitoring treatment effects and early detection of oesophageal squamous cell carcinoma was also depicted by Luo et al .…”
Section: Discussionmentioning
confidence: 99%
“…could show that higher ccfDNA levels after oesophagectomy are associated with poorer disease free survival of oesophageal squamous cell carcinoma patients 19 . Similar results were obtained by Ueda et al ., who describe the usage of somatic mutations in ccfDNA as a biomarker for post-surgical oesophageal squamous cell carcinoma recurrence 20 . The application of mutational analysis on ccfDNA for monitoring treatment effects and early detection of oesophageal squamous cell carcinoma was also depicted by Luo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Combining these factors could potentially increase the performance of our model if incorporated in the future. Ultimately, differential gene expression and mutation 44,45 may well determine prognostication and treatment pathways 46 , but we are likely years from this being universally available. Until then clinical and histopathological data remains the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, high concordance of multiple somatic mutations was found between plasma ctDNA and tumor (primary or metastases) DNA (83%-100%). The allele frequencies of the mutations increased with tumor burden and preceded radiologic evidence of tumor recurrence by 6 months [34]. www.oncotarget.com In 29 patients with localized esophageal carcinoma treated with chemoradiotherapy, baseline ctDNA levels (NGS-based CAPP-seq) were correlated with metabolic tumor volume and squamous histology.…”
Section: Esophageal Carcinomamentioning
confidence: 99%